Exercise oxygen pulse kinetics in patients with hypertrophic cardiomyopathy. Issue 20 (10th March 2022) - Mapelli, Massimo; Romani, Simona; Magrì, Damiano; Merlo, Marco; Cittar, Marco; Masè, Marco; Muratori, Manuela; Gallo, Giovanna; Sclafani, Matteo; Carriere, Cosimo; Zaffalon, Denise; Salvioni, Elisabetta; et al.
Abstract : Objectives: Reduced cardiac output (CO) has been considered crucial in symptoms' genesis in hypertrophic cardiomyopathy (HCM). Absolute value and temporal behaviour of O2 -pulse (oxygen uptake/heart rate (VO2 /HR)), and the VO2 /work relationship during exercise reflect closely stroke volume (SV) and CO changes, respectively. We hypothesise that adding O2 -pulse absolute value and kinetics, and VO2 /work relationship to standard cardiopulmonary exercise testing (CPET) could help identify more exercise-limited patients with HCM. Methods: CPETs were performed in 3 HCM dedicated clinical units. We retrospectively enrolled non-end-stage consecutive patients with HCM, grouped according to left ventricle outflow tract obstruction (LVOTO) at rest or during Valsalva manoeuvre (72% of patients with LVOTO <30; 10% between 30 and 49 and 18% ≥50 mm Hg). We evaluated the CPET response in HCM focusing on parameters strongly associated with SV and CO, such as O2 -pulse and VO2, respectively, considering their absolute values and temporal behaviour during exercise. Results: We included 312 patients (70% males, age 49±18 years). Peak VO2 (percentage of predicted), O2 -pulse and ventilation to carbon dioxide production (VE/VCO2 ) slope did not change across LVOTO groups. Ninety-six (31%) patients with HCM presented an abnormal O2 -pulse temporal behaviour, irrespective of LVOTO values. These patients showed lower peak systolic pressure, workload (106±45 vs 130±49 W), VO2 (21.3±6.6 vs 24.1±7.7 mL/min/kg; 74%±17% vs 80%±20%) and O2 -pulse (12 (9–14) vs 14 (11–17) mL/beat), with higher VE/VCO2 slope (28 (25–31) vs 27 (24–31)) (p<0.005 for all). Only 2 patients had an abnormal VO2 /work slope. Conclusion: None of the frequently used CPET parameters, either as absolute values or dynamic relationships, were associated with LVOTO. Differently, an abnormal temporal behaviour of O2 -pulse during exercise, which is strongly related to inadequate SV increase, correlates with reduced functional capacity (peak and anaerobic threshold VO2 and workload) and increased VE/VCO2 slope, identifying more advanced disease irrespectively of LVOTO.